Density and Distribution of Gastropods in Mangrove Forests of Concong Dalam Village, Indragiri Hilir, Riau Province - Adriman, Adriman; Fauzi, Muhammad; Miracle, Glori (Jurnal Perikanan dan Kelautan, 2025)
Gastropods are mangrove organisms that act as bioindicators in mangrove ecosystems. Mangroves are called productive areas because they are rich in organic matter, which is a source of food and shelter for various biota, such as molluscs and other organisms. Human-induced pressure will cause damage to the mangrove ecosystem. The destruction of the mangrove ecosystem will affect the life of all biota that live in it, including gastropods. This study aims to determine the density and distribution pattern of gastropods in the mangrove area of Concong Dalam Village. This research was carried out in August-September 2024 in Concong Dalam Village. The method used in this study is the survey method. The data obtained is then calculated and analyzed. The results of the study show that there are 11 species of gastropods, nine genera, and six families, including Potamididae (3 types), Neritidae (2 types), Littorinidae (2 types), Ellobidae (1 type), Melogenidae (1 type), and Muricidae (1 type). The six types of mangroves found in this study are Rhizophora apiculata, R. mucronata, Bruguiera cylindrica, Avicennia alba, Sonneratia alba, and Nypa fruticans. The density value of gastropods obtained in Concong Dalam Village ranges from 2.67 – 11.39 ind/m2. The distribution pattern found in Concong Dalam Village is uniform, with an id value of 0.31-0.44. The density of mangroves in Concong Dalam Village ranges from 600 to 1967 p/ha, with the damage criteria being very good